Temperature and water availability effects on radiation and water use efficiencies in alfalfa (Medicago sativa L.) - Collino, D. J. (2005)
Alfalfa, the most important forage crop in Argentina, shows considerable variability in forage production caused by variations in inter-annual rainfall and intra-annual radiation and temperature regimes. Such variation may affect radiation use efficiency and water use efficiency. This paper seeks to study the effects of temperature and water availability on radiation use efficiency and water use efficiency. We conducted the experiment in Córdoba, Argentina, under irrigated and draughted conditions. Drought was imposed by mobile rainout shelters during 3 consecutive periods. We measured forage, intercepted photosynthetically active radiation and water use to calculate radiation use efficiency and water use efficiency between cuttings. Under irrigation, radiation use efficiency and water use efficiency normalised by daytime vapour pressure deficit, were not limited by mean temperature above 21.3 and 21.9°C, respectively. Below those critical values, both variables decreased consistently with temperature decrements. Under drought, radiation use efficiency tended to decrease and water use efficiency tended to increase. In addition, the relationship between relative dry matter and relative water use was not linear, as reported in previous studies for annual crops.